Cultura material e as sociedades da fase marajoara: possibilidades para o ensino de História no Ensino Fundamental II - COSTA, Mayco Bruno Cruz (Universidade Federal do Pará, 2023)
In the Marajó archipelago, between the years 400 and 1300, the Marajoara Indigenous people developed societies noticeable for a material culture that indicated, among other aspects, the management of natural resources with the construction of “tesos”, besides a sophisticated ceramic production. They were among the efforts to build a national identity as representatives of Brazilianness, with reproduction and reframing, in contemporary productions, of the symbolisms in their material culture, as in ceramic pieces produced in the neighborhood of Paracuri, in Icoaraci (Belém-PA). Addressing the theme “Marajoara Culture” was considered relevant in line with the legal statute Lei nº 11.645/2008 and the guidelines of the BNCC, with 6th grade students of elementary school II, in a school located in the city of Ananindeua (PA) - a State School of Elementary and Secondary Education in Pará. A didactic action plan was organized in order to give these students the opportunity to get in touch with cultural material from the societies of the Marajoara period, in “History Workshops” that presented these historical sources in various supports (photographs, a playful game, in addition to excerpts from archaeological research) and visitation classes, visiting two memory spaces: the Research Campus of “Museu Paraense Emílio Goeldi” and “Museu Forte do Presépio”. From these experiences, it was possible to observe learning in history through the application of a diagnostic instrument at two different times with the students – one before and one after the plan for didactic action–, as well as in the reports of visits to the museums, produced by students. There was a change of mind in the identification and contextualization of the specificities in the social dynamics of the studied societies, as well as in the understanding of the importance of their legacy and in the recognition of their artistic traits in contemporary productions. In order to share knowledge, experiences and didactic resources resulting from the research, a website was setup, aiming to contribute with methodological suggestions for teaching this theme.